Analisis keterampilan short service backhand pada bulutangkis - Muaflah, Achmad Alvian; Indarto, Pungki (Universitas Hamzanwadi, 2023)
The ability to hit short service backhand in the badminton UKM Muhammadiyah Surakarta University is not known at the level of athlete's ability. The purpose of this study was to determine the ability level of short service backhand. This research is a quantitative descriptive research with a survey method. The instrument used is the badminton short service test. The population is 60 people, the sampling technique in this study uses a purposive sampling technique so that the total sample is 40 people. The data analysis technique used in this study is percentage descriptive statistics. The result of this study is the